Компаративний аналіз управління соціальною відповідальністю підприємств: зарубіжний досвід - Дюжев, Віктор Геннадійович; Подрез, Ольга Іванівна; Дюжев, Олександр Вікторович (ТОВ "Міжнародний бізнес центр", 2024)
Метою дослідження є аналіз управління соціальною відповідальністю підприємств й держави загалом у розвинутих країнах світу. Побудовано схему взаємозв’язку локальної соціальної відповідальності, що складається із зовнішньої й внутрішньої та діє на рівні підприємства, й регіону, галузі, держави. Обґрунтовано критерії, за якими проведено аналіз, – соціальний захист, послуги, управління за рівнями (державний, місцевий і рівень підприємства). Доведено, що управління соціальною відповідальністю здійснюється у країнах відповідно моделей, які вибрано державою згідно із традиціями й культурою, що відрізняються рівнем втручання з боку органів державноївлади стосовно соціального захисту й надання соціальних послуг.

Building the concept of a socially responsible enterprise is an important element of the process of implementing sustainable development at enterprises and in the country as a whole. The purpose of the paper is the analysis and systematization of key aspects of social protection, provision of social services, organization and management of social responsibility of enterprises, organizations and the state as a whole in developed countries of the world in order to develop a mechanism of social responsibility management in Ukraine. To achieve the goal, the following tasks have been set to research modern approaches to social protection and the provision of social services in foreign countries of the world, as well as to analyze the best foreign practices in managing social responsibility at the enterprise, local and state levels. A scheme of interconnection of local social responsibility, consisting of external and internal and operating at the level of the enterprise, region, industry, and state, has been built. The scheme made it possible to substantiate the criteria by which the analysis was carried out - social protection, social services, management of social responsibility by levels (state, local and enterprise or organization level). It was concluded that the management of social responsibility is carried out in countries according to the models of social responsibility chosen by the state in accordance with traditions and culture. At the same time, there is no single classification of these models. The classifications differ only in the complete disclosure of the European model. It has been proven that the models of social responsibility differ in the level of intervention by state authorities regarding social protection and the provision of social services. The conducted comparative analysis will allow to build a mechanism for managing the social responsibility of the enterprise.
Comparative analysis of corporate social responsibility management: foreign experience
Keywords: соціальна відповідальність підприємства; соціальна відповідальність країни; управління соціальною відповідальністю; розвинуті країни; країни перехідної економіки; країни, що розвиваються; social responsibility of the enterprise; social responsibility of the country; social responsibility management; developed countries; transition economy countries; developing countries